2019
DOI: 10.2478/raon-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Increased cystatin F levels correlate with decreased cytotoxicity of cytotoxic T cells

Abstract: BackgroundCystatin F is a protein inhibitor of cysteine peptidases, expressed predominantly in immune cells and localised in endosomal/lysosomal compartments. In cytotoxic immune cells cystatin F inhibits both the major pro-granzyme convertases, cathepsins C and H that activate granzymes, and cathepsin L, that acts as perforin activator. Since perforin and granzymes are crucial molecules for target cell killing by cytotoxic lymphocytes, defects in the activation of either granzymes or perforin can affect their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
(93 reference statements)
1
25
0
Order By: Relevance
“…All of these studies demonstrated uptake by cells that do not express endogenous cystatin F. In NK cells that express endogenous cystatin F, extracellular cystatin F uptake was demonstrated to potentiate the suppressive function of endogenous cystatin F regarding granzyme function and cell cytotoxicity [13]. As the internalised cystatin F in cystatin F-expressing cells must compete with endogenous intracellular cystatin F, the target peptidases might differ between internalised and endogenous cystatin F. However, here we demonstrate that the target of internalised extracellular cystatin F in TALL-104 cells is also cathepsin C, similar to endogenous cystatin F that also forms immune complexes with cathepsin C [11,16].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…All of these studies demonstrated uptake by cells that do not express endogenous cystatin F. In NK cells that express endogenous cystatin F, extracellular cystatin F uptake was demonstrated to potentiate the suppressive function of endogenous cystatin F regarding granzyme function and cell cytotoxicity [13]. As the internalised cystatin F in cystatin F-expressing cells must compete with endogenous intracellular cystatin F, the target peptidases might differ between internalised and endogenous cystatin F. However, here we demonstrate that the target of internalised extracellular cystatin F in TALL-104 cells is also cathepsin C, similar to endogenous cystatin F that also forms immune complexes with cathepsin C [11,16].…”
Section: Discussionmentioning
confidence: 70%
“…We first assessed recombinant cystatin F uptake into TALL-104 cells, a model cell line of cytotoxic T lymphocytes [16]. Western blot analysis demonstrated that his-tag-labelled recombinant cystatin F is indeed internalised into TALL-104 cells (Figure 1a,b).…”
Section: Extracellular Cystatin F Is Internalised Into Tall-104 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous cysteine cathepsin inhibitor, cystatin F, is a major regulator of cathepsin C, H, and L activities in cytotoxic immune cells (84, 85, 236). Notably, when a state of functional anergy was induced, in either NK cells or CTL, cystatin F levels increased, while levels of cathepsins C, H, L, and granzyme B levels and activities declined (84, 236). Even though cystatin F is, to a greater extent, targeted to endosomes, part of it is secreted as an inactive dimer.…”
Section: Cysteine Cathepsins In Lymphoid Cells—regulating Immune Cellmentioning
confidence: 99%